Macrofauna epígea de besouros coprófilos em sistema de integração lavoura-pecuária - Jamhour, Jorge (2016)
The soil macrofauna (organisms ≥ 2.0 mm) main function is to act indirectly on the decomposition of organic matter and control the population of microorganisms. This study aims to evaluate the density and richness of coprphilic dung beetles at different levels of nitrogen fertilization and grazing pressure on Crop-Livestock Integration System (ILP) and his opposition to morphotypes present in the native forests of the region. Was used a rural area in Abelardo Luz city, western state of Santa Catarina, on the border of southwest of Paraná, 26° 31' 18.8832" south latitude and 52° 15' 3.4986' west longitude and elevation 862 m for the installation of the experiment, which is already carried out the activity of agriculture and livestock. The study is part of the Integrated Project of Long Duration GISPA UTFPR Group, which evaluates the grazing pressure and time of fertilization deployed in April 2013. The experimental design was a randomized complete block design in a 2x2 factorial arrangement with three replications. The factors were "Nitrogen Application" (NP = N in the pasture and NG = N applied in corn) and "Height Grazing" (high and low). The native forest, which provided the parameters for assessing the degree of conservation, lies 700 meters northeast of the experimental area. Modified pitfall traps were used at ground level, on the bait trap and covered together to prevent dehydration. They were carried out 36 collections in bushland, within one year from 26 April 2013, in which we obtained a total of 16,301 individuals and 28 morphotypes. In ILP area specimens were collected from June to September 2014, totaling 23 collections, 74,586 individuals and 30 morphotypes. To carry out the statistics and faunal analysis, GENES programs were used, ANAFAU, NTIA/EMBRAPA and SigmaPlot version 12.5. Most of the correlations observed (90%) between the variables of insects and environmental conditions was significant. The largest number of insects was directly related to the temperature rise. There was a positive correlation between the application of nitrogen and the occurrence of coprophilous. There was a positive correlation between the number of insects and low grazing height. It was also found that some of the insects migrate from the culture to the area of native forest after reaching their peak population. The great similarity of results observed in the native forest and the ILP System indicates the ecological benefits of adopting this technology.